LEGAL PROTECTION OF DEBTORS IN FISHING GEAR PROCUREMENT AGREEMENTS FROM A MAQASHID PERSPECTIVE SYARI'AH - Rosikhan Anwar; Muh Syaifudin (TAWASUT, 2025)
This study aims to describe the problems and impacts of the procurement of fishing gear in the Bonang Subdistrict, Demak Regency community in terms of maqashid shari'ah. Efforts can be made to improve the fishing gear procurement agreement to comply with applicable laws. This research uses a legal sociology or empirical juridical research approach. The data collection techniques used are observation, documentation, and interviews. The results of this study indicate that Legal problems that occur in the fishing gear procurement agreement in Bonang Sub-District, Demak Regency, arise for several reasons: the debtor does not have capital, the deal is only made based on mutual trust, there is no black on white. The capital provider gets a share of 1 crew member every time the juragan goes to sea with the principal debt still the debtor's responsibility (juragan). The creditor does not want to because he will no longer receive a share of the crew when the debt is repaid. In addition, it often happens that when the jagan goes bankrupt and the fishing gear is sold, the debtor does not return the total amount of money, sometimes only 50 percent. Agreements in conventional law are regulated in Article 1320 of the Civil Code. Meanwhile, in Sharia economic law, the agreement leads to usury because an addition (mbageni) in the debt and credit agreement for procuring fishing gear is detrimental to the debtor.